2018
DOI: 10.1055/s-0038-1676589
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-Evoked Increases in Intra-Platelet Zinc Couple to Functional Responses

Abstract: Background  Zinc (Zn 2+ ) is an essential trace element that regulates intracellular processes in multiple cell types. While the role of Zn 2+ as a platelet agonist is known, its secondary messenger activity in platelets has not been demonstrated. Objectives  This article determines whether cytosolic Zn 2+ concentrations ([Zn 2+ ] i ) change in platelets in response to agonist stimulation, in a manner consistent with a secondary messenger, and correlates the effects of [Zn 2+ ] i changes on activation markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 51 publications
(61 reference statements)
1
31
0
Order By: Relevance
“…[10,11] Recent work has demonstrated that intracellular Zn 2+ ([Zn 2+ ]i) increases in the platelet cytosol as a result of agonist stimulation, an a manner consistent with a secondary messenger. [12] In this work it was shown that agonistevoked increases in [Zn 2+ ]i were sensitive to the platelet redox state, suggestive of a role for thiol groups on Zn 2+ binding proteins.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…[10,11] Recent work has demonstrated that intracellular Zn 2+ ([Zn 2+ ]i) increases in the platelet cytosol as a result of agonist stimulation, an a manner consistent with a secondary messenger. [12] In this work it was shown that agonistevoked increases in [Zn 2+ ]i were sensitive to the platelet redox state, suggestive of a role for thiol groups on Zn 2+ binding proteins.…”
Section: Introductionmentioning
confidence: 66%
“…Zn 2+ is present in platelet α granules and also in the platelet cytosol where it is likely to associate with cation-binding proteins [12]. Platelet activation results in increases in cytosolic Zn 2+ concentration, consistent with release from intracellular stores.…”
Section: [Zn 2+ ]I Is Required For Agonist Dependent Ros Releasementioning
confidence: 79%
See 3 more Smart Citations